Social Ethics In The Perspective Of Hadith: Relevance And Application In The New Media Era - Mumtaz Muizza, Muhammad Ahmad; Al Ayubi, Sholahuddin; Fateha, Tazkia Nur; Kamilah, Siti Waspiatul (Wardah, 2024)
This research explores the application and relevance of social ethics in the perspective of hadith in the new media era, aiming to understand how ethical principles can be applied in increasingly complex digital communication. Using qualitative methods and literature studies, the study identifies important aspects of healthy communication, such as polite language selection, information verification, and respect for individual privacy. In the context of new media, good speech serves as an indicator of faith, where individuals who maintain speech tend to show a higher level of faith. In addition, responsibility for content shared on social media is essential for creating a safe and positive communication environment. The study also highlights the importance of respecting differences of opinion and creating inclusive discussion spaces to enrich social interactions. By applying ethical values in every interaction, social media users are expected to contribute to the development of a better and harmonious digital society, providing valuable insights for individuals in improving communication ethics in the new media era.